Measure Device of Water Content On Food Materials Based On Internet of Things - Tri Ferga Prasetyo; Abghi Firas Isdiana; Harun Sujadi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Water content is the amount of water contained in an object, such as soil, agricultural materials, and others. Determination of the water content of a food is very important so that the processing and distribution process gets the right handling. Because if there is improper handling in the processing and determination of the wrong water content there will be damage to food that can be harmful to health. Therefore measuring the amount of water content in food is important. Android-based water level measurement is a tool that provides information on water content in food based on the Internet of Things. This tool is controlled by the Wemos D1 Mini microcontroller by using a Soil Moisture sensor whose output is displayed on the LCD and the android application